QUALITY OF LIFE AND MOTIVATION AT WORK: decisive factor in organizational performance - Lorando, Tatiane Roberta dos Santos Pires; Sapienza, Rodrigo; Costa, Elvio Carlos da (Revista Interface Tecnológica, 2020)
In business organizations, quality of life and motivation corroborate to an environment with profitable production, to a more competitive action and especially to a healthy life for employees. The focus on Quality of Work Life - QWL has been a fundamental aspect of many companies, which are based on the well-being of each employee and on organizational efficiency. Following the competitive business environment, organizations seek to develop more humane conditions, promoting the satisfaction of the entire team, something that will be crucial to the increase of production and will provide qualitative internal processes, considering the interlacing of the organization / company, quality of life at work and productivity. For the development of this article, bibliographic research was carried out, which showed us that in relation to competitiveness, it is essential that productive activities are linked to the organizational structure, optimizing resources, that is why QVT demonstrates the importance of performance and cooperation between employees and the company, where top management observes the needs of the team and promotes improvements in order to motivate and satisfy the employees who give return in quality and productivity, thus promoting the company’s success.